Participatory democracy in grass root level : the pattern of participation in Election of three Unions of Chittagong Hill Tracts - Roy, Srabasti (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.